Assessing Spatio-Temporal Change and Dynamics of Forest Ecosystem Succession Using Patch Analysis - SİVRİKAYA, Fatih; ÇAKIR, Günay (Kastamonu University, 2023)
Aim of study: This study focuses on creating a secondary forest succession (SFS) map between 1972 and 2014 according to the Clementsian theory based on land cover, assessing the spatio-temporal pattern of forest succession change, and determining the factors affecting the forest ecosystem.
Area of study: This study was conducted at the Çermik Forest Enterprise (FE) in Diyarbakır city, located in the Southeastern Anatolia Region of Türkiye.
Material and methods: Clementsian theory, Remote Sensing (RS), and Geographical Information System (GIS) were used to generate the SFS map. Patch Analyst 4.0 was used to determine changes in spatiotemporal patterns with landscape indices.
Main results: The total forested area increased from 32405.1 ha (13% of the study area) in 1972 to 45054.7 ha (18% of the study area) in 2014, with a net increase of 12649.6 ha. It was determined that the progressive succession area was 87736.7 ha, the regressive succession area was 39216.5 ha, and the unchanged succession area was approximately 129989.6 ha. The number of patches increased over a 42-year period.
Research highlights: The forest ecosystem was more fragmented, with patches becoming more irregular, complex, and edgy
Keywords: 2. Zero hunger; 13. Climate action; 15. Life on land